People with a Future: Jesus’ Teaching on Poverty and the Role of Poor People in Christian Churches today - Kügler, Joachim; Chitando, Ezra; Gunda, Masiiwa R. (Prophets, Profits, and the Bible in Zimbabwe: Festschrift for Aynos Masotcha Moyo, 2013)
The article focuses on the beatitude of the poor in the social and religious context of historical Jesus. The original version of this makarism has to be seen as a religious statement which is not meant as a program of social reform. Yet it has political and socio-ethical implications as it connects the poor with God and his kingdom. Those who are searching God have to go to the poor. A possible function of the beatitude of the poor in the struggle against poverty can be seen in the spiritual empowerment it gives to the poor themselves: Poverty is against God’s will; it is no divine punishment and does not separate from God. The poor are people with a future; they will be liberated from suffering. Poverty has no place in God’s Kingdom but will be eradicated.
free